Birth Experience Mediates the Association Between Fear of Childbirth and Mother-Child-Bonding Up to 14 Months Postpartum: Findings From the Prospective Cohort Study DREAM - Seefeld, Lara; Weise, Victoria; Kopp, Marie; Knappe, Susanne; Garthus-Niegel, Susan (Frontiers in Psychiatry, 2022)
Objective: To explore the longitudinal associations between prepartum fear of childbirth (FOC), birth experience, and postpartum mother-child-bonding, and the potential mediator role of the birth experience. Design: Women from the prospective cohort study DREAM completed questionnaires during pregnancy, 8 weeks, and 14 months after the birth. Participants: A community sample of n = 645 pregnant women from a large city in Eastern Germany participated in the study. Results: In a regression analysis, FOC predicted negative birth experience (β = .208, p < .001) which in turn predicted poorer mother-child-bonding both at 8 weeks (β = .312, p < .001) and 14 months postpartum (β = .200, p < .001). FOC also predicted mother-child-bonding at 14 months postpartum (β = .098, p < .05). Of note, this association was mediated by birth experience both at 8 weeks, indirect effect ab = 0.065, 95% CI [0.036, 0.098], and 14 months postpartum, indirect effect ab = 0.043, 95% CI [0.023, 0.067]. These effects remained stable even when adjusting for potential confounders. Key conclusions: This study suggests that the association between FOC and mother-child-bonding is mediated by birth experience, pointing to the importance of a woman’s positive subjective experience. Implications for practice: Findings reveal two targets for peripartum interventions for women at risk for poor mother-child-bonding, namely the implementation of FOC screenings during pregnancy, and birth experience as mediating factor between FOC and mother-child-bonding. Focusing on the mother’s subjective birth experience could aid to identify women at risk for impaired bonding who might need additional support.